LEADERSHIP SKILLS IN THE 21st CENTURY OF SCHOOL ADMINISTRATOR: NEW APPROACH, NEW QUALITY - Kerdsiri, Kanyaphat; Sathtrukram, Thitiporn; Choobuakaw, Panuwat; Wongsirasawat, Chanchai; Faisong, Suwit (Journal of MCU Nakhondhat, 2023)
The world in the 21st century is a time of rapid change. both in terms of economy, society, politics, technology, environment and the digital world There is a quick communication. Affect the planning and setting guidelines for national development. School administrators in today’s world Therefore, it must be a professional manager. have high leadership skills and a leader of change therefore leading educational institutions to survive and overcome the crisis that arises School administrators in the 21st century, which consist of 10 skills as follows: 1) Communication Skill, 2) Ability to Manage Organization Skill, 3) Determination of Direction Skill, 4) Understanding one’s own strengths and weaknesses Skill, 5) Delicacy in work Skill, 6) Use of technology, innovation and digitalization, 7) Teamwork Skill, 8) Judgmental skills, 9) Focus on results, and 10), developing others skill, would be successful in educational institute management. Thus, if school administrators adhere to the skills of school administrators in the 21st century, all 10 skills can lead educational institutions to develop towards their desired goals. Operate in the same direction in line with supervision, monitoring, measurement and evaluation of performance according to indicators that set educational standards. establishing a quality assurance system for all levels of education To lead to the development of educational quality standards, 3 educational quality standards, concretely, efficiently and effectively. By linking it in line with the policy drive of the Office of the Basic Education Commission, a new way, a quality way, it will surely be successful in school management. It is accepted both inside and outside the school. Keep up with the changes in the 21st century world.